Q: What is 12.0905 ln word form?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

ln(a) = 5.3 a = e5.3

X = 1.31356+0.612045*iSteps to solve, take the natural log of both sides:ln(X^(3-5i)) = ln(23-14i).(3-5i)*ln(X) = ln(23-14i). Convert 23-14i to exponential form: A*e^(iÃŽËœ) {A = 26.926 and ÃŽËœ = -0.54679 radians}(3-5i)*ln(X) = ln(A*e^(iÃŽËœ))= ln(A) + iÃŽËœ = ln(26.926) - 0.54679i.divide by (3-5i): ln(X) = (ln(A) + iÃŽËœ) / (3-5i) = (3.2931 - 0.54679i)/(3-5i)So we have ln(X) = 0.370978 + 0.436033i, then:e^(ln(X)) = e^(0.370978 + 0.436033i) --> X = 1.31356+0.612045*i

That is because prime numbers do not follow any known pattern. However, the number of primes smaller than a number n is approximately n/ln(n) where ln is the natural logarithm.And the word for comparisons is "than" not "then".That is because prime numbers do not follow any known pattern. However, the number of primes smaller than a number n is approximately n/ln(n) where ln is the natural logarithm.And the word for comparisons is "than" not "then".That is because prime numbers do not follow any known pattern. However, the number of primes smaller than a number n is approximately n/ln(n) where ln is the natural logarithm.And the word for comparisons is "than" not "then".That is because prime numbers do not follow any known pattern. However, the number of primes smaller than a number n is approximately n/ln(n) where ln is the natural logarithm.And the word for comparisons is "than" not "then".

18

Take the natural logarithm (ln) of both sides of the equation to cancel the exponent (e). For example, ify=Aexlog transform both sides and apply the rules of logarithms:ln(y)=ln(Aex)ln(y)=ln(A)+ln(ex)ln(y)=ln(A)+xrearrange in terms of x:x=ln(y)-ln(A), or more simplyx=ln(y/A)

Related questions

ln(a) = 5.3 a = e5.3

ln

Natural log

An exponential function is of the form y = a^x, where a is a constant. The inverse of this is x = a^y --> y = ln(x)/ln(a), where ln() means the natural log.

Ln 4 + 3Ln x = 5Ln 2 Ln 4 + Ln x3= Ln 25 = Ln 32 Ln x3= Ln 32 - Ln 4 = Ln (32/4) = Ln 8= Ln 2

X = 1.31356+0.612045*iSteps to solve, take the natural log of both sides:ln(X^(3-5i)) = ln(23-14i).(3-5i)*ln(X) = ln(23-14i). Convert 23-14i to exponential form: A*e^(iÃŽËœ) {A = 26.926 and ÃŽËœ = -0.54679 radians}(3-5i)*ln(X) = ln(A*e^(iÃŽËœ))= ln(A) + iÃŽËœ = ln(26.926) - 0.54679i.divide by (3-5i): ln(X) = (ln(A) + iÃŽËœ) / (3-5i) = (3.2931 - 0.54679i)/(3-5i)So we have ln(X) = 0.370978 + 0.436033i, then:e^(ln(X)) = e^(0.370978 + 0.436033i) --> X = 1.31356+0.612045*i

That is because prime numbers do not follow any known pattern. However, the number of primes smaller than a number n is approximately n/ln(n) where ln is the natural logarithm.And the word for comparisons is "than" not "then".That is because prime numbers do not follow any known pattern. However, the number of primes smaller than a number n is approximately n/ln(n) where ln is the natural logarithm.And the word for comparisons is "than" not "then".That is because prime numbers do not follow any known pattern. However, the number of primes smaller than a number n is approximately n/ln(n) where ln is the natural logarithm.And the word for comparisons is "than" not "then".That is because prime numbers do not follow any known pattern. However, the number of primes smaller than a number n is approximately n/ln(n) where ln is the natural logarithm.And the word for comparisons is "than" not "then".

18

ln(ln)

Take the natural logarithm (ln) of both sides of the equation to cancel the exponent (e). For example, ify=Aexlog transform both sides and apply the rules of logarithms:ln(y)=ln(Aex)ln(y)=ln(A)+ln(ex)ln(y)=ln(A)+xrearrange in terms of x:x=ln(y)-ln(A), or more simplyx=ln(y/A)

Use the product rule.y = x lnxy' = x (ln x)' + x' (ln x) = x (1/x) + 1 ln x = 1 + ln xUse the product rule.y = x lnxy' = x (ln x)' + x' (ln x) = x (1/x) + 1 ln x = 1 + ln xUse the product rule.y = x lnxy' = x (ln x)' + x' (ln x) = x (1/x) + 1 ln x = 1 + ln xUse the product rule.y = x lnxy' = x (ln x)' + x' (ln x) = x (1/x) + 1 ln x = 1 + ln x

2 ln(9) + 2 ln(5) = 2 ln(x) - 3ln(81) + ln(25) = ln(x2) - 37.61332 = ln(x2) - 3ln(x2) = 10.61332ln(x) = 5.30666x = e5.30666 = 201.676 (rounded)